Verify (-11)x{(-5)+(-7)}={(-11)x(–5)}+{(-11)x(-7)}​

Question

Verify (-11)x{(-5)+(-7)}={(-11)x(–5)}+{(-11)x(-7)}​

in progress 0
Parker 3 weeks 2021-11-06T08:25:36+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-11-06T08:27:00+00:00

    Answer:

    Step-by-step explanation:

    According to distributive property:

    a(b+c) = ab+ ac

    (-11) x {(-5)+(-7)} = {(-11) x (-5)} + {(-11)x(-7)}

    (-11) x (-5-7) = (55) + (77)

    (-11) x (-12) = 132

    132=132

    Hence verified

    Hope this helps….

    0
    2021-11-06T08:27:29+00:00

    <body bgcolor=black><marquee direction="side"><font color=orange>

    FOR STEPS REFER TO ATTACHMENT

    <body bgcolor=black><marquee direction="up"><font color=blue>

    PLZ LIKE THE ANSWER AND MARK IT AS BRAINLIEST

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )